Effect of growth temperature on defects in epitaxial GaN film grown by plasma assisted molecular beam epitaxy - S. S. Kushvaha; P. Pal; A. K. Shukla; Amish G. Joshi; Govind Gupta; M. Kumar; S. Singh; Bipin K. Gupta; D. Haranath (AIP Advances, 2014)
We report the effect of growth temperature on defect states of GaN epitaxial layers grown on 3.5 μm thick GaN epi-layer on sapphire (0001) substrates using plasma assisted molecular beam epitaxy. The GaN samples grown at three different substrate temperatures at 730, 740 and 750 °C were characterized using atomic force microscopy and photoluminescence spectroscopy. The atomic force microscopy images of these samples show the presence of small surface and large hexagonal pits on the GaN film surfaces. The surface defect density of high temperature grown sample is smaller (4.0 × 108 cm−2 at 750 °C) than that of the low temperature grown sample (1.1 × 109 cm−2 at 730 °C). A correlation between growth temperature and concentration of deep centre defect states from photoluminescence spectra is also presented. The GaN film grown at 750 °C exhibits the lowest defect concentration which confirms that the growth temperature strongly influences the surface morphology and affects the optical properties of the GaN epitaxial films.